An Analytical Study of the Socio-Cultural Impact of Atheism in Pakistan - Mehboob Hussain; Dr. Intikhab Ahmad (Journal of Religion and Society, 2026)
This article examines the impact of atheism (Ilhād) on Pakistani society, focusing on its intellectual, social, moral, and psychological dimensions. In a country where religion has historically shaped collective identity, social norms, and ethical values, the emergence and spread of atheistic thought present significant challenges. The study analyzes the factors contributing to the rise of atheistic tendencies, including globalization, digital media influence, secular education trends, and socio-economic frustrations. It argues that the weakening of religious commitment affects family structures, moral responsibility, and social cohesionThe research further explores how atheistic narratives influence youth perceptions regarding faith, purpose, and morality, often leading to identity conflicts and value relativism. By examining contemporary social patterns, the article highlights correlations between declining spiritual engagement and increasing moral ambiguity, social fragmentation, and cultural disorientation.From an Islamic perspective, the study underscores the role of faith, accountability, and moral discipline in maintaining societal balance. It concludes that constructive dialogue, intellectual engagement, educational reform, and strengthening religious literacy are essential to address the growing influence of atheism. The article provides insights for scholars, educators, and policymakers seeking to understand and respond to this evolving ideological trend within Pakistani society. This study analyzes the factors that contribute to the rise of atheistic tendencies, including global trends (globalization), the influence of digital media, secular educational trends, and socio-economic frustrations. The paper emphasizes that a decline in religious commitment negatively affects family structure, moral responsibility, and social cohesion. Keyword: Atheism، Pakistani Society، Socio-Cultural Impact، Religious Identity، Intellectual Trends